Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah Bank BRI Cabang Sukoharjo - Riantoro, Ahmad, Nur Achmad, S.E, M.Si (2016)
This study aims to mngetahui impact of service quality on customer loyalty. Also to know how big the impact of service quality on customer loyalty. The analysis tool used is multiple linear regression, by retrieving data using questionnaires at the respondent bank customers BRI branch Sukoharjo. The results of this study indicate that the quality of service consisting of empathy and physical evidence partially influence on customer loyalty, while reliability, assurance and responsiveness not partial effect. Quality of service together greatly affect the quality of service, it is shown from the results of the F test of 10.676 with a significance level of 0.000. Quality of service is able to explain the loyalty of customers by 54,8%. Thus businesses should pay attention to the quality of service in order to control the market.